Analisis Perbandingan Biaya dan Waktu Antara Flexible Pavement dan Cakar Ayam Modifikasi : (Studi Kasus Jalan Sekar Putih Kota Mojokerto) - Iwan Kuswanto (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
This research discusses the evaluation of the Sekar Putih road pavement structure in Mojokerto City, which often experiences damage due to unstable ground contours and heavy traffic loads, especially when used as an alternative route. Repeated damage causes a significant burden on the maintenance budget every year. To overcome this problem, the value engineering method is applied as a systematic approach in determining the most efficient type of construction in terms of cost and time without reducing the quality and function of the road. In this research, two road pavement systems were compared, namely the Modified Chicken Claw (CAM) foundation and flexible pavement. Through this comparative analysis, it is hoped that a more economical road construction solution will be found, able to extend the life of the road plan, and reduce maintenance costs in the future. This research also plays a role in supporting more sustainable infrastructure planning for the Mojokerto region which is developing rapidly as part of the Pintukertosusila metropolitan area.